Molecular dynamics simulation and experimental study into effect of temperature on hardness of ice abrasives - Li, Zhiping; Liu, Yong; Wei, Jianping; Wu, Jiaojiao (Frontiers in Earth Science, 2023)
Ice abrasive jet technology is a green and environmentally friendly process with wide application prospects in the field of surface treatment. Ice abrasive jets constitute an essential technical parameter of the process, and temperature affects the hardness of ice. In this study, for clarifying relationship between the temperature and ice particles, the molecular dynamics method was used to simulate the dynamic characteristics of ice at different temperatures, and the hardness of ice at different temperatures was measured. As the temperature increased, the dynamic characteristics of ice changed correspondingly, and the intermolecular hydrogen bonds and van der Waals interactions of ice weakened. From a chemical perspective, with the increase in temperature the intermolecular force weakens, the lattice energy of the crystal decreases, the resistance required to destroy the crystal decreases, and the crystal exhibits low hardness. Temperature affects the hardness of ice by changing the strength of the intermolecular force. To further clarify the law of ice hardness variation with temperature, in this study, the hardness of ice was measured at different temperatures and divided into five grades. A linear simulation of the temperature and hardness was also performed, and a strong linear correlation was found between temperature and hardness. In this study, numerical simulations were performed and experimental results were analyzed to identify the effect of temperature on the hardness of ice by changing the force between ice molecules, which is crucial for improving the erosion efficiency of ice abrasive jets.